In The Polarized Field Of Synthetic Fibres Improving Emulsification - Jamoliddin Arabov; Khusankhon Bobojanov; Jamila Ergashova; Shoaziz Shorakhmedov (Genius Journals, 2024)
This paper proposes an emulsification device in a new improved method of antistatic processing of synthetic fibres. The priorities of the influencing factors in the device were taken as the magnitude of the polarized field voltage, the distance between the fieldgenerating electrodes, and the percentage of emulsion, and their change intervals were determined experimentally. The analysis of the mechanical properties of the yarns obtained from the cotton-Nitron blending showed that the elongation of the cotton fibre was lower than that of the nitron fibre, while the yarn strength was much higher in the 80/20 cotton-Nitron blending and the yarn strength in the 50/50 cotton-Nitron blending was lower. It should be noted that in the cotton-Nitron blending, the stiffness of the yarn decreases as the bundles of Nitron fibres increase by up to 50%. The use of the proposed emulsification device effectively recycles fibrous materials, reduces the electrification of the fibre and improves the quality of the yarn obtained from them. Fibres are dielectric, ie synthetic fibres have polarization properties with very low friction, and it has been found that emulsification of fibres in an improved way to reduce it is highly effective. In order to obtain high-quality yarn from the cotton-nitron blends, a high-strength yarn technology was developed from 20 and 30% nitron blending emulsified in an improved way.
Keywords: Nitron fibres; synthetic fibres; polarization properties